A new hybrid polyhedral cubic silsesquioxane chemically modified with 4-amino-5-(4-pyridyl)-4H-1,2,4-triazole-3-thiol (APTT) and copper hexacyanoferrate(III) for voltammetric determination of nitrite - Soares, Layciane Aparecida [UNESP]; da Silveira, Tayla Fernanda Serantoni [UNESP]; Silvestrini, Daniela Rodrigues [UNESP]; de Oliveira Bicalho, Urquisa [UNESP]; Filho, Newton Luiz Dias [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (My University, 2013)
This paper describes the preparation, and voltammetric application of a hybrid nanocomposite formed by interaction of a octa(3-chloropropyl)octasilsesquioxane (SS) modified with 4-amino-5-4 (pyridyl)-4H-1,2,4-triazole-3-thiol (SA), and its subsequent reactions in two steps, first with copper and so hexacyanoferrate (III) (CuHSA). The precursors and CuHSA were initially characterized by by Fourier transform infrared spectra (FTIR). This composite was incorporated into a graphite paste electrode and the electrochemical behavior studies were conducted with cyclic voltammetry. The cyclic voltammogram of the modified graphite paste electrode with CuHSA, showed one redox couple with formal potential Eθ'= 0.75V vs Ag/AgCl(sat) (KCl 1.0 mol L-1; v = 20 mV s-1) attributed to the redox process Fe(II)(CN)6 / Fe(III)(CN)6 of the binuclear complex formed. The redox couple presents an electrocatalytic response for determination of nitrite. The modified graphite paste electrode showed a linear response of 1.0 × 10-5 to 5.0 × 10-3 mol L-1. The method has a detection limit of 3.57 × 10-4 mol L-1, standard deviation of 1.5% for n=3 with an amperometric sensitivity 30.00 mA/mol L-1 to nitrite. The modified electrode was electrochemically stable and showed good reproducibility. © 2013 by ESG.
Keywords: 4-amino-5-4(pyridyl)-4H-1,2,4-triazole-3-thiol; Electrocatalysis; Nitrite; Octa(3-chloropropyl)octasilsesquioxane; Voltammetry